The study of hemorrhoid cases in children in Amir-Kabir and Bahrami hospitals, 1362-78 - Poorang H (Tehran University Medical Journal, 2000)
Hemorrhoid is one of the anorectal disorders in children, which is reported to be complication of portal hypertension. This condition is not common in children. We found only 7 cases from 30000 operation done in Tehran university hospital on pediatric group between 1983-99. The main complain of these 7 cases was anorectal mass (43%) and pain due to thrombosis (28.5%) treatment of all 7 cases was successful and no other pathology found.